Modern Pesantren: Shaping Future Leaders Based on Islamic Values - Nisa, Durotun; Purnomo, Joko (Faculty of Education and Teacher Training of UINSI Samarinda, 2025)
This research aims to analyze the educational strategies implemented at Al-Kautsar Islamic Boarding School in shaping future leaders based on Islamic values. The main focus of this study includes three aspects: strengthening foreign languages, integration of religious and general subjects, and a contextual approach through evaluation and self-development of santri. This research used a qualitative method with a case study approach. Data were collected through in-depth interviews with caregivers, teachers, and santri, as well as observation and documentation. Data analysis techniques used the Miles and Huberman interactive model, which consists of three main steps, namely data reduction, data presentation, and conclusion drawing. The results showed that foreign language strengthening is carried out through language zone programs and international student exchanges. Santri are accustomed to using Arabic and English actively in daily life, which aims to form self-confidence and global da'wah abilities. This strategy creates an immersive environment that encourages natural and contextualized language use. The integration of religious and general studies is implemented by inserting Islamic values in science and technology materials, so that students are able to see science as part of the signs of Allah's greatness. Meanwhile, the contextual approach and evaluation system based on Islamic values are carried out through weekly muhasabah, moral evaluation, and continuous character building. This strategy plays an important role in shaping the personality of students who are disciplined, responsible, and have good character.